Nursing Pharmacology (Open textbook library., 2020)
This open access Nursing Pharmacology textbook is designed for entry-level undergraduate nursing students. It explains basic concepts of pharmacology and describes common medication classes. This book is not intended to be used as a drug reference book, but direct links are provided to DailyMed, which provides trustworthy information about marketed drugs in the United States.